Combined effects of vitamin E and omega-3 fatty acids on protecting ambient PM2.5-induced cardiovascular injury in rats. (April 2017) - Du, Xihao; Jiang, Shuo; Bo, Liang; Liu, Jie; Zeng, Xuejiao; Xie, Yuquan; He, Qing; Ye, Xingwang; Song, Weiming; Zhao, Jinzhuo
Abstract: Objective: This study aims to observe whether the combined treatment with vitamin E (vit E) and omega-3 polyunsaturated fatty acids (Ω-3 FA) could prevent the fine particulate matter (PM2.5 )-induced cardiovascular injury through alleviating inflammation and oxidative stress. At the same time, the appropriate combination dosage of vit E and Ω-3 FA was explored to find an optimized protective dose to protect the injury induced by PM2.5 . Methods: The SD rats were pretreated with different concentration of vit E and Ω-3 FA separately or jointly. Then the rats were exposed to ambient PM2.5 by intratracheal instillation for three times. The expression of tumor necrosis factor α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6) in serum and supernatant of cardiac tissue were detected by ELISA kits. The levels of malondialdehyde (MDA), superoxide Dismutase (SOD) and glutathione-peroxidase (GSH-Px) in myocardium and the level of MDA in serum were measured. Meanwhile, the cardiac injury was evaluated by histopathological examination. Results: Compared with the severe injury of rats in PM2.5 exposure group, the rats in vit E or Ω-3 FA-pretreated groups had a slighter injury in heart. Meanwhile, pretreatment with vit E or Ω-3 FA induced a significantly alleviation of the inflammatory cytokines (TNF-α, IL-1β, IL-6) and the elevation of the anti-oxidative activity especially in the rats pretreated with combined vit E and Ω-3 FA. In addition, the combined protecting effects of vit E and Ω-3 FA showed a dose-dependent manner. Conclusion: Supplementation with vit E and Ω-3 FA could protect the PM2.5 -induced injury, and the combination of vit E and Ω-3 FA might produce more effective effects than the separate nutrient did. Highlights: We explore the protective function of supplementary nutrients in PM2.5 induced cardiovascular injury. Inflammation, oxidative stress and dense inflammatory cell infiltrations in PM2.5 exposed rats are alleviated after intervened with nutrients, especially in the combined treatment groups. There is a combined action between vitamin E and Ω-3 fatty acids.